Resiliensi Holistik Dalam Pelayanan Misi: Pengalaman Keluarga Misionaris Indonesia Di Kyrgyzstan - Apner Ndapa Behar; Lie Ja Hwe (Pusat Studi Pentakosta Indonesia, 2025)
Missionary service in challenging regions such as Kyrgyzstan imposes psychological, cultural, and social pressures on Indonesian missionary families. Obstacles such as isolation, cultural differences, and limited support from sending churches require an understanding of the formation of missionary family resilience. This study aims to examine the resilience of Indonesian missionary families in Kyrgyzstan, the factors influencing it, and effective pastoral support strategies. A qualitative approach was used through in-depth interviews with three missionary families, along with data triangulation from fellow missionaries, local church councils, and sponsored children. The results indicate that missionary family resilience is shaped by spirituality, family harmony, and support from both local communities and international partners. Adaptation strategies such as language learning and cultural appreciation are important for successful inculturation and contextual ministry. The lack of a member care system from sending churches highlights the need to strengthen spiritual guidance and ongoing emotional support.AbstrakPelayanan misi di wilayah menantang seperti Kyrgyzstan menimbulkan tekanan psikologis, budaya, dan sosial bagi keluarga misionaris Indonesia. Hambatan seperti isolasi, perbedaan budaya, dan minimnya dukungan gereja pengutus menuntut pemahaman tentang pembentukan resiliensi keluarga misionaris. Penelitian ini bertujuan mengkaji resiliensi keluarga misionaris Indonesia di Kyrgyzstan, faktor yang mempengaruhinya, dan strategi dukungan pastoral yang efektif. Pendekatan kualitatif digunakan melalui wawancara mendalam dengan tiga keluarga misionaris, triangulasi data dari rekan misionaris, majelis gereja lokal, dan anak asuh. Adapun hasil penelitian menunjukan bahwa Resiliensi keluarga misionaris terbentuk melalui spiritualitas, keharmonisan keluarga, dan dukungan komunitas lokal maupun mitra internasional. Strategi adaptasi seperti pembelajaran bahasa dan penghargaan budaya penting untuk keberhasilan inkulturasi dan pelayanan kontekstual. Kurangnya sistem member care dari gereja pengutus menunjukkan perlunya penguatan pendampingan rohani dan dukungan emosional berkelanjutan.